Targeting canonical TGFβ/SMAD3 and ERK1/2 signaling in human valve interstitial cells to modulate immune-fibrotic responses in rheumatic heart disease - Charan Sai Ramireddi; Mohit K. Rai; Anjali Singh; Vikas Agarwal; Surendra K. Agarwal; Alok Kumar; Shantanu Pande (Journal of Physiology and Biochemistry, 2026)

Compound droughts as emergent outcomes of cascading drought propagation - Prashant Prashant; Surendra Kumar Mishra; Anil Kumar Lohani; Vijay P. Singh (Journal of Hydrology, 2026)

A holistic index for hydrological characterization of catchments - Prashant Prashant; Surendra Kumar Mishra; Anil Kumar Lohani; Vijay P. Singh (Journal of Hydrology, 2026)

Struvite-enhanced nutrient recovery and microbial dynamics in biochar-amended manure-based bioponic systems for circular nutrient management - Sumeth Wongkiew; Suchana Amnuaychaichana; Pongsak (Lek) Noophan; K.C. Surendra; Samir Kumar Khanal (Journal of Environmental Chemical Engineering, 2026)

Convolution neural network-based estimation of high-resolution urban canopy parameters for urban climate modelling - Kshama Gupta; Kakali Deka; Surendra Kumar Sharma; Ashutosh Bhardwaj; Sandeep Maithani; Raghavendra Pratap Singh (Urban Climate, 2026)

Upcycling single-use polyethylene terephthalate plastics waste into oxygen-rich CQDs for enhanced photoelectrocatalytic two-electron ORR: Mechanistic insights into selective H2O2 generation - Surendra Saini; Mukul Sethi; Priyanka Meena; Aditya Gurjar; Krishan Kumar; D.K. Mahawar; Sana Ullah; Dirk Ziegenbalg; Sven Rau; Vijay Parewa (Chemical Engineering Journal, 2026)

Comparative pilot-scale hydrodynamic cavitation-assisted methanol- and ethanol-based biodiesel production from waste cooking oil: Process performance and techno-economic analysis - Nirav Prajapati; Surendra Singh Kachhwaha; Pravin Kodgire; Rakesh Kumar Vij; Jeffrey S. Cross (Bioresource Technology Reports, 2026)

Permethrin resistance and associated mutations in Pune, Maharashtra (Detection of permethrin resistance and associated mutations in Aedes aegypti mosquitoes in Pune Municipal Corporation, Maharashtra) - Surendra Kumar; Samyak Moon; Prajwal Gaikwad; Ashwini Ramdasi; Riddhi Rawlani; Mehrunnisa Raje; Prudhvi Lal Bhukya; Sreelakshmi PR (International Journal of Tropical Insect Science, 2026)

Nilotinib-loaded hydroxy propyl β-cyclodextrin nanosponges for improved oral bioavailability in chronic myeloid leukemia therapy - Bhagya Buela Gudipalli; Surendra AV; Ramakrishna Kakarla; Datta Maroti Pawde; Avinash Kumar G; Udaykumar Thummala; Shailendra Singh; Chakravarthi Guntupalli; Buchi N. Nalluri; Sona Muthu madaswamy; Kasi Viswanadh matte (DARU Journal of Pharmaceutical Sciences, 2026)

Optimizing Soil Health and Productivity in Intensive Rice-Wheat Systems Using Conjoint Application of Sewage Sludge - Surendra Singh Jatav; Satish Kumar Singh; Debabrata Nath; Vandana Kumari; Pramod Kumar Sharma (Bulletin of Environmental Contamination and Toxicology, 2026)

Aridity Index-Integrated First-Order Planar Regression Framework for Refining Curve Number in a Medium-Scale Watershed - Prashant Prashant; Surendra Kumar Mishra; Anil Kumar Lohani (Water Resources Management, 2026)

Genetic characteristics and connectivity of the southernmost snow leopard populations in the Indian Himalayan Region: Conservation implications - Sujeet Kumar Singh; Bheem Dutt Joshi; Reeta Sharma; Rahul De; Jouni Aspi; Laura Kvist; Aishwarya Maheshwari; Tawqir Bashir; Diwakar Sharma; Mukesh Thakur; Manoj Kumar; Indranil Mondal; et al. (Mammalian Biology, 2026)

Ethno-medicinal uses, ecology, phytochemistry, biological activities, and conservation approaches for Himalayan Rhubarb species - Ashish Kumar; Arun K. Jugran; Surendra Singh Bargali; Indra D. Bhatt (Natural Product Research, 2026)

Commercially Viable Biodiesel Production from High-FFA acid oils Using Pilot-Scale Hydrodynamic Cavitation - Nirav Prajapati; Surendra Singh Kachhwaha; Pravin Kodgire; Rakesh Kumar Vij; Jeffrey S. Cross (BioEnergy Research, 2026)

Ecological vulnerability and phytochemical richness of Rheum australe in the Indian Himalayan Region: insights for conservation - Ashish Kumar; Neha Thapliyal; Arun K. Jugran; Surendra Singh Bargali; Indra D. Bhatt (Plant Biosystems, 2026)

Targeting NF-κB and JAK/STAT pathways in rheumatoid arthritis: emerging nanocarrier-based drug delivery approaches - G. Surendra; Jeetendra Kumar Gupta; E. Susithra; A. C. Jesudoss Prabhakaran; A. Jasmine Chandra; Vijayakumar Subash; Thukani Sathanantham Shanmugarajan; Uppuluri Varuna Naga Venkata Arjun; Konatham Teja Kumar Reddy; Ramana Hechhu (Inflammopharmacology, 2026)

Screening of NPASS library to uncover potential Dipeptidyl peptidase-IV enzyme inhibitors using structure-based virtual screening and molecular dynamics - Surendra Kumar Gautam; Kailash Jangid; Bharti Devi; Nikita Kumari (In Silico Pharmacology, 2026)

Carbon sequestration and mineralization kinetics under long-term rice–wheat system in a Himalayan Mollisol - Riaj Rahaman; Sunanda Biswas; D. K. Singh; Priya Singh; Kalyani Patil; Suman Kumar Surendra (Plant and Soil, 2026)

A Deep Learning Approach for Automated Building Footprint Extraction from Cartosat Imagery - Kakali Deka; Kshama Gupta; Surendra Kumar Sharma; Ashutosh Bhardwaj; Bhoomika Ghale; Sandeep Maithani (Journal of the Indian Society of Remote Sensing, 2026)

Impatiens Violoides Edgew. ex Hook.f. an Endangered Species New Addition to Flora of Uttarakhand - Praveen Kumar Verma; Shivam Kishwan; Rajendra Kumar Meena; Surendra Singh Bisht; Anup Chandra (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2026)

Indoor 3D geometry estimation using single panorama image - Surendra Kumar Sharma; Kamal Jain; Anoop Kumar Shukla (Applied Geomatics, 2026)

Anaerobic co-digestion as a strategy for treating coffee Pulp: Insights into process performance - Renisha Karki; K.C. Surendra; Steven Skerlos; Lutgarde Raskin; Samir Kumar Khanal (Bioresource Technology, 2026)

A campaign-based study on the physio-chemical characterization and source apportionment of particulate matter in the Central Himalayas - Vikas Rawat; Narendra Singh; Surendra K. Dhaka; Prashant K. Chauhan; Jagdish C. Kuniyal; Prity S. Pippal; Sanjeev Kimothi; Mayank Kumar Chauhan (Environmental Science and Pollution Research, 2025)

Unlocking higher performance of dual-ion storage via fluorene substitution in bipolar conjugated polymers featuring dual acceptors - Dhananjaya Patra; Shuvajit Ghosh; Rakesh Parida; Subir Kumar Pati; Surendra K. Martha; Jin Yong Lee; Sungjune Park (Chemical Engineering Journal, 2025)

Molecular characterization and phylogenetic insights into Theileria annulata affecting cattle in Western Uttar Pradesh, India - Vishnu Kumar Rai; Arbind Singh; Amit Kumar Verma; Prem Sagar Maurya; Vikas Jaiswal; Ramakant; Surendra Upadhyay; Ayush Pal (Tropical Animal Health and Production, 2025)

GC–MS profiling and computational analysis of Balanites aegyptiaca phytoconstituents for antidiabetic activity: insights from network pharmacology and molecular docking - Surendra Kumar Gautam; Rakesh Kumar Paul; Smita Jain; Vipin Kumar; Kaisar Raza (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Monitoring of antibacterial capabilities of biosynthesized gold nanoparticles facilitated cyanobacterium, Spirulina subsalsa, against MDR pathogenic bacteria - Shuvasree Bej; Surendra Swain; Ajit Kumar Bishoyi; Chita Ranjan Sahoo; Bigyan Ranjan Jali; Rabindra Nath Padhy (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Detection of manganese (II) by PVP-AgNPs for water monitoring - Shailja Pandey; Shipra Mital Gupta; Surendra Kumar Sharma (Environmental Monitoring and Assessment, 2025)

Enhanced bioethanol production from sequential alkali-laccase-hydroxybenzotriazole pretreatment and additive-mediated saccharification in kenaf (Hibiscus cannabinus L.) - Laxmi Sharma; Pratik Satya; Binita Dev; Tinku Goswami; Nurnabi Meherul Alam; Suman Roy; Arvind Kumar Singh; Surendra Kumar Pandey; Bijan Majumdar; A.K. Lavanya; Gouranga Kar (Biomass and Bioenergy, 2025)

Split quadrant mosaic algorithm: a novel approach to develop multi-model ensemble for wind resource assessment - Garlapati Nagababu; Preksha Patwa; Harish Puppala; V. V. Arun Kumar Surisetty; Surendra Singh Kachhwaha; Rashmi Sharma (Climate Dynamics, 2025)

Immunomodulator and marker-assisted identification of Allium genotypes containing immunological memory against anthracnose - Kuldip Jayaswall; Deepesh Kumar; Deepanshu Jayaswal; R. Sagar; Sanjay Kumar; Ram Kumar Sharma; Kiran Bhagat; Vijay Mahajan; Himanshu Sharma; Surendra Pratap Singh; Isha sharma (Physiological and Molecular Plant Pathology, 2025)

Macroalgae-derived bioactive compounds for functional food and pharmaceutical applications—a critical review - Manpreet Kaur; Ty Shitanaka; K.C Surendra; Samir Kumar Khanal (Critical Reviews in Food Science and Nutrition, 2025)

In-situ intermittent micro-aeration in food waste and sewage sludge anaerobic co-digestion: Performance, stability, and microbial dynamics - Wachiranon Chuenchart; Christelle Sawaya; K.C. Surendra; Adam L. Smith; Samir Kumar Khanal (Bioresource Technology, 2025)

Efficient Remediation of Cr(VI) in Soil by Polypyrrole Modified Corn-Stover Biochar - Yiping Guo; Weijie Feng; Qianqian Zhang; Wanfei Shao; Xiangkai Tao; Weigao Zhao; Sang-Hyoun Kim; K. C. Surendra; Samir Kumar Khanal (Water, Air, & Soil Pollution, 2025)

Building Extraction for Urban Infrastructure Mapping Using Deep Neural Networks and High-Resolution Remote Sensing Data - Surendra Kumar Sharma; Vivek Sharma; Vishal Mishra (Journal of the Indian Society of Remote Sensing, 2025)

Mechanistic and metabolic exploration of neohesperidin against lung cancer cell lines through ROS-mediated mitochondrial apoptosis: An in-silico and in-vitro approach - Ruchi Pandey; Khushboo Choudhary; Surendra Rajit Prasad; Pranesh Kumar; Priya Bisht; Dande Aishwarya; Pallaprolu Nikhil; Sachindra Kumar; Ramalingam Peraman; Nitesh Kumar (Toxicology and Applied Pharmacology, 2025)

Recent Advances in Aquaponic Systems: A Critical Review - Shreeja Lopchan Lama; Kyle Rafael Marcelino; Sumeth Wongkiew; K. C. Surendra; Zhen Hu; Jae Woo Lee; Samir Kumar Khanal (Reviews in Aquaculture, 2025)
Aquaponics, a symbiotic farming of plants and fish, is a promising solution to address global food security. While aquaponics contributes to nutrient recovery, water reclamation, and reduced land and freshwater use, achieving consistent and economically viable production remains a substantial challenge. Several key issues in aquaponics include maintaining optimal water quality and dissolved oxygen concentration, delivering a balanced nutrient profile for plants, and managing solids accumulation. However, recent advances in new system designs, algal co‐cultivation, micro‐nanobubble technology, biofilter media, as well as system automation coupled with the Internet of Things, Artificial Intelligence, and robotics can improve the performance of these systems. Moreover, a greater understanding of the microbiome across various components of an aquaponic system is important in improving symbiotic relationships and supporting favorable ecological dynamics. This, in turn, promotes improved nutrient cycling, plant and fish growth, and overall system performance. This review highlights several such advances, critically analyzing the challenges faced during operation, and offers future research directions. Through discussion on current knowledge gaps in system operation, technological integration, and understanding of microbiomes, this review aims to provide a comprehensive framework for advancing aquaponic systems and outline potential directions for future innovations.

Cross-equatorial travelling ionospheric disturbances and changes in background ionospheric densities over Indian longitudes during geomagnetic storm of 20–21 December 2015 - Sovan Saha; Duggirala Pallamraju; Sunil Kumar; V.Lakshmi Narayanan; Surendra Sunda (Advances in Space Research, 2025)

Retraction notice to “Microbial dynamics for lignocellulosic waste bioconversion and its importance with modern circular economy, challenges and future perspectives” [Bioresour. Technol. 291 (2019) 121905] - Surendra Sarsaiya; Archana Jain; Sanjeev Kumar Awasthi; Yumin Duan; Mukesh Kumar Awasthi; Jingshan Shi (Bioresource Technology, 2025)

Retraction notice to “Improving methane yield and quality via co-digestion of cow dung mixed with food waste” [Bioresour. Technol. 251 (2018) 259–263] - Sanjeev Kumar Awasthi; Rutu Joshi; Hiya Dhar; Shivpal Verma; Mukesh Kumar Awasthi; Sunita Varjani; Surendra Sarsaiya; Zengqiang Zhang; Sunil Kumar (Bioresource Technology, 2025)

Retraction notice to “Changes in global trends in food waste composting: Research challenges and opportunities” [Bioresour. Technol. 299 (2020) 122555] - Sanjeev Kumar Awasthi; Surendra Sarsaiya; Mukesh Kumar Awasthi; Tao Liu; Junchao Zhao; Sunil Kumar; Zengqiang Zhang (Bioresource Technology, 2025)

Retraction notice to “Recovery of value-added products from biowaste: A review” [Bioresour. Technol. 360 (2022) 127565] - Yuwen Zhou; Vinay Kumar; Sharareh Harirchi; V.S. Vigneswaran; Karthik Rajendran; Pooja Sharma; Yen Wah Tong; Parameswaran Binod; Raveendran Sindhu; Surendra Sarsaiya; Deepanraj Balakrishnan; M. Mofijur; et al. (Bioresource Technology, 2025)

Identification of a Stable Drought-Tolerant High-Yielding Line for Chickpea Crop Improvement - Santosh Kumar Gupta; Vikas Dwivedi; Nandakumar Surendra Kute; Philip Francis; Swarup Kumar Parida; Debasis Chattopadhyay (Plant Molecular Biology Reporter, 2025)

Dual-nutrient stress tolerance in wheat is regulated by nitrogen and phosphorus uptake, assimilation, reutilization, and differential expression of candidate genes - Renu Pandey; Sandeep Sharma; Ankita Mishra; Akshay Sureshrao Sakhare; Surendra Kumar Meena; Krishnapriya Vengavasi (Plant and Soil, 2025)

Potential application of endophytic bacteria for induction of abiotic stress tolerance in plants - Hemant Kumar; Rusi Lata; Uzma Khan; James F. White; Surendra Kumar Gond (Symbiosis, 2025)

Senescence-associated genes (SAGs) in cotton: Genome-wide identification, phylogenetic, and expression analyses provide insight into their role in development and stress response - Varsha Singh; Maninder Singh; Tikshana Yadav; Rishi Kumar Verma; Mamta Yadav; Vijay Pratap Singh; Samir V. Sawant; Surendra Pratap Singh (South African Journal of Botany, 2025)

Enhancing spatial resolution of Landsat derived land surface temperature: A novel downscaling approach using an extreme learning machine - Jidnyasa Patil; Sandeep Maithani; Surendra Kumar Sharma (Journal of Earth System Science, 2024)

Effect of groundwater nutrients on coastal phytoplankton community composition in the Bay of Bengal, India: An experimental study - D. Bhaskara Rao; T. Surendra; Ch.N.V. Laxmi; K.M. Meera; G.V.M. Gupta; B.S.K. Kumar (Marine Pollution Bulletin, 2024)

Evidence in Reaching Consensus in Usage of Mandibular Advancement Device for Pre- and Post-obstructive Sleep Apnea Treatment with Blood and Salivary Inflammatory Biomarkers Profiles - Thakur Prasad Chaturvedi; Pooja Priyadarshani; Vipul Kumar Sharma; Ishita Shrivastava; Deepak Singh; Surendra Pratap Mishra; Navneet Kumar Dubey (Sleep and Vigilance, 2024)

Biosynthesis and characterisations of silver nanoparticles with filamentous cyanobacterium Lyngbya sp. with in vitro antibacterial properties against MDR pathogenic bacteria - Surendra Swain; Shuvasree Bej; Ajit Kumar Bishoyi; Bigyan Ranjan Jali; Rabindra Nath Padhy (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Linking curve number with environmental flows: a novel approach - Shailendra Kumar Kumre; Sabyasachi Swain; Kumar Amrit; Surendra Kumar Mishra; Ashish Pandey (Environmental Science and Pollution Research, 2024)

Synergies of co-infecting pathogens, sea lice (Lepeophetheirus salmonis) and Moritella viscosa, are impacted by exposure order, and host response to initial infection - Wenlong Cai; Liang Zhong; Kathleen Parrish; Surendra Kumar; Khalil Eslamloo; Eyesun Fajei; Shona K. Whyte; Sara L. Purcell; Ladan Jahangiri; Runsheng Li; Albert Caballero Solares; Richard G. Taylor; et al. (Aquaculture, 2024)

Exploration of oncolytic drugs from endophytic fungi of Catharanthus roseus - Uzma Khan; Rusi Lata; Hemant Kumar; Surendra Kumar Gond (South African Journal of Botany, 2024)

Wet and dry spell induced changes in the soil CO2 effluxes of Pine and Oak ecosystems of Central Himalaya: a comparative assessment for monsoon and winter seasons - Sandipan Mukherjee; Priyanka Lohani; Srabanti Ballav; Pooja Mehta; K. Chandra Sekar; Sumit Pundir; Kireet Kumar; Surendra Pratap Singh (Environmental Monitoring and Assessment, 2024)

Index for refining soil health assessment through multivariate approach under diverse agro-climatic zones in the Indo-Gangetic basin of Bihar - Debabrata Nath; Ranjan Laik; Anup Das; Biswajit Pramanick; Panneerselvam Peramaiyan; Santosh Kumar Singh; Vandana Kumari; Surendra Singh Jatav; Abdus Sattar (Science of The Total Environment, 2024)

Detection of vinblastine and related bioactive compounds from culture extracts of endophytic fungi of Catharanthus roseus - Uzma Khan; Surendra Kumar Gond (World Journal of Microbiology and Biotechnology, 2024)

Investigating climate and land use change impacts on design flood estimation over Indian tropical catchments - Ishan Sharma; Sabyasachi Swain; Surendra Kumar Mishra; Ashish Pandey (Tropical Ecology, 2024)

3D point cloud reconstruction using panoramic images - Surendra Kumar Sharma; Kamal Jain; Anoop Kumar Shukla (Applied Geomatics, 2024)
Panorama photogrammetry, the process of analyzing panoramic images, has gained popularity in close-range photogrammetry for 3D reconstruction over the past decade. Initially, researchers utilized cylindrical or spherical panoramic images created through specialized cameras or conventional ones with rectilinear lenses. However, these methods were hindered by the high cost of panorama equipment and the need for manual reconstruction. Consequently, there's a growing demand for automated algorithms capable of reconstructing 3D point clouds from stitched panorama images. This study aims to provide a cost-effective solution for automatic 3D point cloud reconstruction from panoramas. The study is divided into two parts; it first outlines an image acquisition strategy for capturing overlapping perspective images to facilitate accurate panorama generation. Subsequently, it introduces an automated algorithm for 3D point cloud reconstruction from panorama images. The process utilizes the KAZE feature detector for feature detection and introduces a novel feature matching approach for matching panorama images. Accuracy assessment of the reconstructed 3D point clouds was done using three methods: Line Segment Based approach, yielding RMSE errors of 34.2mm and 39mm for dataset-1 and dataset-2 respectively, No-Reference 3D Point Cloud Quality Assessment, resulting in quality scores of 8.5939 and 7.4535 for dataset-1 and dataset-2 respectively, and M3C2 distance method computed value of 0.091059 and 0.165179 respectively, indicating high quality of the generated point clouds.

Structural and Luminescent Properties of Dy(III) Doped Ca0.5Bi3P2O10 Nanophosphors for Solid-State Lighting & Latent Fingerprinting Applications - Diksha Solanki; Poonam Devi; Hina Dalal; Neeraj Sehrawat; Mukesh Kumar; Surendra Kumar; Rajesh Kumar Malik (Journal of Fluorescence, 2024)

Modulation of brain energy metabolism in hepatic encephalopathy: impact of glucose metabolic dysfunction - Shambhu Kumar Prasad; Arup Acharjee; Vishal Vikram Singh; Surendra Kumar Trigun; Papia Acharjee (Metabolic Brain Disease, 2024)

Deciphering the morphological, phytochemical, genetic diversity, and niche distribution of Allium stracheyi Baker (Amaryllidaceae): An economically important culinary herb of Western Himalaya, India - Ashish Kumar; Arun K. Jugran; Kuldeep Joshi; Indra D. Bhatt; Surendra Singh Bargali (South African Journal of Botany, 2024)

Blue light perceiving CRY proteins: protecting plants from DNA damage - Priya Gahlowt; Durgesh Kumar Tripathi; Surendra Pratap Singh; Ravi Gupta; Vijay Pratap Singh (Plant Cell Reports, 2024)

Temporal dynamics of urban air pollutants and their correlation with associated meteorological parameters: an investigation in northern Indian cities - Pushpendra Singh Soni; Vikram Singh; Alok Sagar Gautam; Karan Singh; Manish Sharma; Rolly Singh; Alka Gautam; Surendra Pratap Singh; Sanjeev Kumar; Sneha Gautam (Environmental Monitoring and Assessment, 2024)

Seed germination and early seedling growth behavior of critically endangered Catamixis baccharoides to variation in soil type - Dixit Kumar Pathak; Kiran Bargali; Surendra Singh Bargali; Archana Fartyal (Vegetos, 2024)

Investigating an empirical approach to predict sediment yield for a design storm: a multi-site multi-variable study - Ishan Sharma; Surendra Kumar Mishra; Ashish Pandey; Henok Mekonnen Aragaw; Vijay P. Singh (Environment, Development and Sustainability, 2024)

Bioponic systems with biochar: Insights into nutrient recovery, heavy metal reduction, and microbial interactions in digestate-based bioponics - Sumeth Wongkiew; Satja Aksorn; Suchana Amnuaychaichana; Chongrak Polprasert; Pongsak Lek Noophan; Vorapot Kanokkantapong; Thammarat Koottatep; K.C. Surendra; Samir Kumar Khanal (Waste Management, 2024)

Genome-wide identification and expression analysis of autophagy-related genes (ATG) in Gossypium spp. reveals their crucial role in stress tolerance - Mamta Yadav; Garima Saxena; Rishi Kumar Verma; Mehar H. Asif; Vijay Pratap Singh; Samir V. Sawant; Surendra Pratap Singh (South African Journal of Botany, 2024)

Spatial assessment of flood vulnerability and waterlogging extent in agricultural lands using RS-GIS and AHP technique—a case study of Patan district Gujarat, India - Nitin Surendra Singh Gahalod; Kumar Rajeev; Pawan Kumar Pant; Sonam Binjola; Rameshwar Lal Yadav; Rang Lal Meena (Environmental Monitoring and Assessment, 2024)

Exploring effect of scale dependency in LST downscaling – using convolution neural network-extreme learning machine (CNN-ELM) - Jidnyasa Patil; Sandeep Maithani; Surendra Kumar Sharma (Earth Science Informatics, 2024)

Sustainable utilization of pineapple fruit waste as a potential source of regenerated cellulose for the development of high-strength paper - Jitendra Kumar; Izhar Alam; Avinash Kumar; Anuj Kumar; Satish Kumar Singh; Surendra Pal Singh; Chhaya Sharma (Biomass and Bioenergy, 2024)

Consumer's behavioural intention towards adoption of e-bike in Kathmandu valley: structural equation modelling analysis - Lakash Kumar Shakya; Niranjan Devkota; Krishna Dhakal; Ramhari Poudyal; Surendra Mahato; Udaya Raj Paudel; Seeprata Parajuli (Environment, Development and Sustainability, 2024)

A highly sensitive electrochemical sensor for Cr6+ ions detection using Ag NPs/rGO/quercetin modified glassy carbon electrode for water applications - G. Surendra Rajkumar; P. Senthil Kumar; Gayathri Rangasamy (Groundwater for Sustainable Development, 2024)

Effect of landforms and vegetations on pedological variability and crop yield along the toposequence of Eastern Coastal Plain of Odisha, India - Srinivasan Ramasamy; Lalitha Manickam; Shelton Padua; Tejashvini Ashwathappa; Jagdish Prasad; Surendra Kumar Singh (Journal of Coastal Conservation, 2024)

Development of Allium cepa potential intron polymorphism markers for molecular breeding of Alliums - Kuldip Jayaswall; R. Sagar; Deepanshu Jayaswal; Akash Kumar; Surendra Pratap Singh; Romit Seth; Himanshu Sharma; Deepesh Kumar; Vijay Mahajan; Sanjay Kumar; Major Singh (South African Journal of Botany, 2024)

A novel environmental friendly and sustainable process for textile dyeing with sulphur dyes for cleaner production - Navneet Singh Shekhawat; Surendra Kumar Patra; Ashok Kumar Patra; Bamaprasad Bag (Chemical Engineering Journal, 2024)

Flow Characterization in Triply-Periodic-Minimal-Surface (TPMS)-Based Porous Geometries: Part 2—Heat Transfer - Surendra Singh Rathore; Balkrishna Mehta; Pradeep Kumar; Mohammad Asfer (Transport in Porous Media, 2024)

Variability of Particulate Amino Acids and Processes Responsible for Sources into the Coastal Waters of the Bay of Bengal - B. S. K. Kumar; D Bhaskara Rao; T. Surendra; Ch. V. Rao; M. P. Meshram (Estuaries and Coasts, 2024)

Morphological and genetic diversity assessment of Rheum australe D. Don – A high value medicinal herb from the Himalaya, and implications for conservation strategies - Ashish Kumar; Yogita Bisht; Kalpana Rautela; Arun K. Jugran; Indra D. Bhatt; Surendra Singh Bargali (South African Journal of Botany, 2023)

Surface mass balance calculation with ground observation in the sub-basin of Larsemann Hills, East Antarctica - Surendra Jat; Mohammad Sadiq; Pradeep Kumar; Abhishek Verma; Deepak Y Gajbhiye (Polar Science, 2023)

Impact estimation of landuse/land cover changes and role of hydrological response unit in hydrological modelling in a watershed of Mahanadi river basin, India - Priyanka Gunjan; Surendra Kumar Mishra; Anil Kumar Lohani; Surendra Kumar Chandniha (Natural Hazards, 2023)

Comparing the Organic Carbon Fractions in Composts of Agricultural Wastes at Different Temperatures and Stages - Ajit Kumar Meena; Dnyaneshwar V. Mali; Ram Swaroop Meena; Surendra Singh Jatav; Ram Hari Meena; Jitendra Singh Bamboriya; Premlata Meena; Shyam D. Jadhao; Abed Alataway; Ahmed Z. Dewidar; Mohamed A. Mattar (Journal of Soil Science and Plant Nutrition, 2023)

A synergetic approach for quantification and analysis of coal fires in Jharia Coalfield, India - Ashwani Raju; Anjali Singh; Surendra Kumar Chandniha (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Synthesis of enhanced hydrophilic UiO-66-(COOH)2/PSF hybrid membrane for efficient separation of o/w and removal of water pollutants - Dashrathbhai B. Kanzariya; Smit Vala; Surendra Sasikumar Jampa; Manish Kumar Sinha; Tapan K. Pal (Journal of Environmental Chemical Engineering, 2023)

A Review of Environmental Flow Assessment Studies in India with Implementation Enabling Factors and Constraints - Ravindra Kumar Verma; Ashish Pandey; Sangeeta Verma; Surendra Kumar Mishra (Ecohydrology & Hydrobiology, 2023)

Recent progression on phytochemicals and pharmacological properties of the filamentous cyanobacterium Lyngbya sp. - Surendra Swain; Shuvasree Bej; Ajit Kumar Bishoyi; Chinmayee Priyadarsani Mandhata; Chita Ranjan Sahoo; Rabindra Nath Padhy (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Utilization of biochar derived from chick pea straw to enhance the properties of black cotton soil - Khemlata Soni; Aryak Shori; Surendra Kalbande; Vipin Kumar Mishra (Bioresource Technology Reports, 2023)

Brucella melitensis: Divergence Among Indian Strains and Genetic Characterization of a Strain Isolated from Cattle - Hariprasad Naidu Gonuguntla; Kota Sri Naga Leela Surendra; Amitesh Prasad; Laxmi Narayan Sarangi; Samir Kumar Rana; Gujjala Manasa; Ponnanna Nadikerianda Muthappa; A. V. Harikumar; Girish Kumar Sharma (Indian Journal of Microbiology, 2023)

Effects of vermicompost leachate on nitrogen, phosphorus, and microbiome in a food waste bioponic system - Sumeth Wongkiew; Chongrak Polprasert; Pongsak (Lek) Noophan; Thammarat Koottatep; Vorapot Kanokkantapong; K.C. Surendra; Samir Kumar Khanal (Journal of Environmental Management, 2023)

Experimental probe into an automative engine run on waste cooking oil biodiesel blend at varying engine speeds - Keshab Biswakarma; Pranjal Sarmah; Prabhu Paramasivam; Seshathiri Dhanasekaran; Surendra Kumar Yadav; Virendra Kumar (Fuel, 2023)

Energy storage and milk chilling performance of metal oxide nanofluids - Ravi Prakash; Manjunatha Mutharayappa; Mahesh Kumar Guruvanna; Heartwin Amaladhas Pushpadass; Menon Rekha Ravindra; Surendra Nath Battula (Food and Bioproducts Processing, 2023)

Dopant-driven recombination delay and ROS enhancement in nanoporous Cd1-xCuxS heterogeneous photocatalyst for the degradation of DR-23 dye under visible light irradiation - Savita Meena; Mukul Sethi; Swati Meena; Pratibha Saini; Krishan Kumar; Surendra Saini; Sumita Shekhawat; Mohan Lal Meena; Anshu Dandia; Shawn D. Lin; Vijay Parewa (Environmental Research, 2023)

Anti-neutrophilic cytoplasmic antibody (ANCA)-associated vasculitis mimicking as cerebral amyloid angiopathy in a 78-year-old gentleman - Surendra Kumar; Naveen Kumar; Iti Chaudhary (Acta Neurologica Belgica, 2023)

Nanobubble technology applications in environmental and agricultural systems: Opportunities and challenges - Kyle Rafael Marcelino; Li Ling; Sumeth Wongkiew; Hua Thai Nhan; K. C. Surendra; Ty Shitanaka; Hui Lu; Samir Kumar Khanal (Critical Reviews in Environmental Science and Technology, 2023)

Wastewater-Associated Infections: A Public Health Concern - Shuvasree Bej; Surendra Swain; Ajit Kumar Bishoyi; Chinmayee Priyadarsani Mandhata; Chita Ranjan Sahoo; Rabindra Nath Padhy (Water, Air, & Soil Pollution, 2023)

Peroxynitrite is essential for aerenchyma formation in rice roots under waterlogging conditions - Pooja Singh; Saumya Jaiswal; Ajayraj Kushwaha; Priya Gahlowt; Vipul Mishra; Durgesh Kumar Tripathi; Surendra Pratap Singh; Ravi Gupta; Vijay Pratap Singh (Planta, 2023)

Plasmonic nanoparticle’s anti-aggregation application in sensor development for water and wastewater analysis - Shailja Pandey; Shipra Mital Gupta; Surendra Kumar Sharma (Environmental Monitoring and Assessment, 2023)

Sensitivity and performance evaluation of improved SCS-CN model by incorporating temporally decaying retention parameter with varying soil moisture for more versatile applications - Nand Kishore Sharma; Ravindra Kumar Verma; Sangeeta Verma; Surendra Kumar Mishra; Ashish Pandey (Paddy and Water Environment, 2023)

Snow crab (Chionoecetes opilio) hemocytes and hepatopancreas transcriptomes: identification, validation, and application of immune-relevant biomarkers of exposure to noise - Jennifer R. Hall; Sarah J. Lehnert; Emmanuel Gonzalez; Jacqueline M. Hanlon; Surendra Kumar; Corey J. Morris; Matthew L. Rise (Frontiers in Marine Science, 2023)
The snow crab ( Chionoecetes opilio ) fishery off the east coast of Newfoundland and Labrador, Canada, has been impacted by annual seismic oil and gas surveying in recent decades, and commercial crab harvesters are concerned that it could potentially affect this resource. A laboratory study was performed to investigate the effects of chronic noise exposure on the transcriptomes of snow crab hemocytes and hepatopancreas, which are important in immunity, metabolism and response to environmental stress. Snow crab were held in replicate control or experimental tanks; on alternating days, the experimental tanks were exposed to noise from an underwater speaker which played a recording of a seismic airgun firing every 10 sec in a continuous loop for ~ 22 weeks (chronic noise). RNA sequencing was used to identify candidate noise-responsive molecular biomarkers in both hemocytes and hepatopancreas. The quantified transcripts of individuals (i.e. n=10 from each of the four groups) were compared using DESeq2, identifying over 300 noise-responsive transcripts in each cell/tissue type. Real-time quantitative polymerase chain reaction (qPCR) assays were designed and run for 61 of these transcripts with significant BLASTx hits. One transcript ( rgs2 ) was significantly (p < 0.05) higher expressed in both hemocytes and hepatopancreas in response to noise; five and seven other transcripts were either significant or showed a non-significant trend of differential expression (0.05 < p ≤ 0.1) in hemocytes (e.g. cfb upregulated, sacs and myof downregulated) and hepatopancreas (e.g. gpx3 and atf3 upregulated, sult1c4 downregulated), respectively. To further investigate the performance and utility of these candidate biomarkers in the field, expression levels of 25 selected transcripts were then examined in the hepatopancreas of snow crab that had been subjected to 2D and 3D seismic surveying using both qPCR and multivariate statistical analyses. Overall, few of these biomarkers showed consistent results in field-collected snow crab, highlighting the need to combine lab and field-based studies to fully evaluate the utility of biomarkers. Nonetheless, our study still identified noise-responsive biomarkers in both settings (including stress and immune relevant genes), providing valuable information for understanding the impact of ocean noise on snow crab physiology and health.

GIS based spatial-temporal distribution of water quality parameters and heavy metals in drinking water: Ecological and health modelling - Elias Bojago; Inderjeet Tyagi; Faheem Ahamad; Surendra Kumar Chandniha (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

A comprehensive review on thermochemical, and biochemical conversion methods of lignocellulosic biomass into valuable end product - Mukesh Kumar Awasthi; Taner Sar; Sarath C. Gowd; Karthik Rajendran; Vinay Kumar; Surendra Sarsaiya; Yue Li; Raveendran Sindhu; Parameswaran Binod; Zengqiang Zhang; Ashok Pandey; Mohammad J. Taherzadeh (Fuel, 2023)

A Procedure for Assessment of Environmental Flows Incorporating Inter- and Intra-Annual Variability in Dam-Regulated Watersheds - Ravindra Kumar Verma; Ashish Pandey; Surendra Kumar Mishra; Vijay P. Singh (Water Resources Management, 2023)

Assessing the impact of climate change on the hydrology of Gidabo river sub-basin, Ethiopian Rift Valley Lakes Basin - Henok Mekonnen Aragaw; Surendra Kumar Mishra; Manmohan Kumar Goel (Sustainable Water Resources Management, 2023)

Killed fungal pathogen triggers antifungal metabolites in Alcaligenes faecalis for plant defense - Shatrupa Ray; Prachi Singh; Jyoti Singh; Surendra Singh; Birinchi Kumar Sarma; Harikesh Bahadur Singh (Physiological and Molecular Plant Pathology, 2023)

Establishment of rainfall partitioning parameters for tea plantations - Chitra Shukla; K. N. Tiwari; Surendra Kumar Mishra (Hydrological Sciences Journal, 2023)

Characterization and assessment of hydrological droughts using GloFAS streamflow data for the Narmada River Basin, India - Sabyasachi Swain; Surendra Kumar Mishra; Ashish Pandey; Prashant Kumar Srivastava; Saswata Nandi (Environmental Science and Pollution Research, 2023)

Recent progress on phytochemistry and pharmacological activities of Grewia asiatica L. (Tiliaceae) and traditional uses - Surendra Swain; Shuvasree Bej; Chinmayee Priyadarsani Mandhata; Ajit Kumar Bishoyi; Chita Ranjan Sahoo; Rabindra Nath Padhy (South African Journal of Botany, 2023)

Green and eco-compatible iron nanocatalysed synthesis of benzimidazole: A review - Surendra Kumar Bagaria; Nidhi Jangir; Dinesh Kumar Jangid (Sustainable Chemistry and Pharmacy, 2023)

Engineered biochar for the effective sorption and remediation of emerging pollutants in the environment - Sutripto Majumder; Pooja Sharma; Surendra Pratap Singh; Ashok Kumar Nadda; Prafulla Kumar Sahoo; Changlei Xia; Swati Sharma; Rajiv Ganguly; Su Shiung Lam; Ki Hyeon Kim (Journal of Environmental Chemical Engineering, 2023)

Efficient CO2/CH4 separation using [Bmim][Ac]/Pebax-1657 supported ionic liquid membranes and its prediction by density functional theory - Tushar Patil; Swapnil Dharaskar; Manish kumar Sinha; Jalaja Pandya; Satyam Shinde; Surendra Sasi kumar Jampa; Mika Sillanpaa; Chang Yoo (International Journal of Greenhouse Gas Control, 2023)

Vector competence of three species of mosquitoes to Ingwavuma virus (Manzanilla orthobunyavirus), a new bunyavirus found circulating in India - Surendra Kumar; P. R. Sreelekshmi; Y. S. Godke; A. B. Sudeep (VirusDisease, 2023)

A thermo-chemical and biotechnological approaches for bamboo waste recycling and conversion to value added product: Towards a zero-waste biorefinery and circular bioeconomy - Zheli Ding; Sanjeev Kumar Awasthi; Manish Kumar; Vinay Kumar; Andrei Mikhailovich Dregulo; Vivek Yadav; Raveendran Sindhu; Parameswaran Binod; Surendra Sarsaiya; Ashok Pandey; Mohammad J. Taherzadeh; Rashmi Rathour; et al. (Fuel, 2023)

Applications of artificial intelligence in anaerobic co-digestion: Recent advances and prospects - Muzammil Khan; Wachiranon Chuenchart; K.C. Surendra; Samir Kumar Khanal (Bioresource Technology, 2023)

Flow Characterization in Triply Periodic Minimal Surface (TPMS)-Based Porous Geometries: Part 1—Hydrodynamics - Surendra Singh Rathore; Balkrishna Mehta; Pradeep Kumar; Mohammad Asfer (Transport in Porous Media, 2023)

SAtellite-based Marine Process Understanding, Development, Research and Applications for Blue Economy (SAMUDRA): A Technology Demonstration Program in the Bay of Bengal - Rashmi Sharma; Neeraj Agarwal; Ratheesh R; Surisetty VVArun Kumar; A. D. Rao; KVSR Prasad; Jaya Kumar Seelam; R. Mani Murali; V. Suneel; Surendra Singh K; R. K. Sarangi; Soba J. Kizhakudan; et al. (Journal of the Indian Society of Remote Sensing, 2023)

Techno-economic Analysis of Wave Energy Resource for India - Ravi P. Patel; Garlapati Nagababu; Surendra Singh Kachhwaha; V. V. Arun Kumar Surisetty; M. Seemanth (Journal of the Indian Society of Remote Sensing, 2023)

Trend Analysis of Nitrogen dioxide (NO2) in Northern Part of India During Paddy Residue Burning Using a Contextual Approach - Sandeep Maithani; Surendra Kumar Sharma (Journal of the Indian Society of Remote Sensing, 2023)

Conservation importance of the strategic, centrally located snow leopard population in the western Himalayas, India: a genetic perspective - Sujeet Kumar Singh; Rahul De; Reeta Sharma; Aishwarya Maheshwari; Bheem Dutt Joshi; Diwakar Sharma; Sambandam Sathyakumar; Bilal Habib; Surendra Prakash Goyal (Mammalian Biology, 2022)

Appraisal of historical trends in maximum and minimum temperature using multiple non-parametric techniques over the agriculture-dominated Narmada Basin, India - Sabyasachi Swain; Surendra Kumar Mishra; Ashish Pandey; Deen Dayal; Prashant Kumar Srivastava (Environmental Monitoring and Assessment, 2022)

Assessment of drought trends and variabilities over the agriculture-dominated Marathwada Region, India - Sabyasachi Swain; Surendra Kumar Mishra; Ashish Pandey; Deen Dayal (Environmental Monitoring and Assessment, 2022)

Mitochondrial cytochrome b indicates the presence of two paraphyletic diverged lineages of the blue sheep Pseudois nayaur across the Indian Himalaya: conservation implications - Bheem Dutt Joshi; Vinay Kumar; Rahul De; Reeta Sharma; Ankita Bhattacharya; Stanzin Dolker; Ranjana Pal; Ved Prakash Kumar; Sambandam Sathyakumar; Bhupendra Singh Adhikari; Bilal Habib; Surendra Prakash Goyal (Molecular Biology Reports, 2022)

Simulation of Land Surface Temperature Patterns Over Future Urban Areas—A Machine Learning Approach - Sandeep Maithani; Garima Nautiyal; Archana Sharma; Surendra Kumar Sharma (Journal of the Indian Society of Remote Sensing, 2022)

Correction to: Hydrogeochemical characterization of groundwater and their associated potential health risks - Anjali Singh; Ashwani Raju; Surendra Kumar Chandniha; Lipi Singh; Inderjeet Tyagi; Rama Rao Karri; Ajay Kumar (Environmental Science and Pollution Research, 2022)

Irrigation potential for optimal cropping pattern in a command area and operational policy - S. B. Ganesh Kumar; B. R. Ramesh; H. J. Surendra (Sustainable Water Resources Management, 2022)

Hydrogeochemical characterization of groundwater and their associated potential health risks - Anjali Singh; Ashwani Raju; Surendra Kumar Chandniha; Lipi Singh; Inderjeet Tyagi; Rama Rao Karri; Ajay Kumar (Environmental Science and Pollution Research, 2022)

Optimal cropping pattern for a tail-end distributary canal of Bhadra command area using linear programming model - S. B. Ganesh Kumar; B. R. Ramesh; H. J. Surendra (Modeling Earth Systems and Environment, 2022)

Identification of Wheat Genotypes Resilient to Terminal Heat Stress Using GGE Biplot Analysis - Kiran Devi; Sulekha Chahal; Karnam Venkatesh; Surendra Singh; Subhash Chandra Tripathi; H. M. Mamrutha; Ruchika Sharma; Sonia Sheoran; Nagendra Kumar Singh; Gyanendra Singh; Gyanendra Pratap Singh; Ratan Tiwari (Journal of Soil Science and Plant Nutrition, 2022)

Predicting the distributional range shifts of Rhizocarpon geographicum (L.) DC. in Indian Himalayan Region under future climate scenarios - Devendra Kumar; Aseesh Pandey; Sandeep Rawat; Mayank Joshi; Rajesh Bajpai; Dalip Kumar Upreti; Surendra Pratap Singh (Environmental Science and Pollution Research, 2022)

Ropanicant (SUVN-911), an α4β2 nicotinic acetylcholine receptor antagonist intended for the treatment of depressive disorders: pharmacological, behavioral, and neurochemical characterization - Ramakrishna Nirogi; Renny Abraham; Pradeep Jayarajan; Venkatesh Goura; Rajesh Kallepalli; Rajesh babu Medapati; Jayaprakash Tadiparthi; Vinod kumar Goyal; Santosh kumar Pandey; Ramkumar Subramanian; Surendra Petlu; Jagadeesh Babu Thentu; et al. (Psychopharmacology, 2022)

Temperature Perturbations in the Troposphere and Lower Stratosphere Over a Semi-arid Region During the 2010 Solar Eclipse - Vinay Kumar; S. B. Surendra Prasad; K. Krishna Reddy; S. K. Dhaka; R. K. Choudhary; M. Venkatarami Reddy; Shu-Peng Ho (Pure and Applied Geophysics, 2022)

Crosstalk and gene expression in microorganisms under metals stress - Pooja Sharma; Ambreen Bano; Ashok Kumar Nadda; Swati Sharma; Sunita Varjani; Surendra Pratap Singh (Archives of Microbiology, 2022)

Consequential rice crop response to resultant soil properties in a toposequence in eastern coastal plain of Odisha, India - Ramasamy Srinivasan; Dulal Chandra Nayak; Rajendran Gobinath; Subbanna Naveen Kumar; D. V. K. Nageswara Rao; Surendra Kumar Singh (Modeling Earth Systems and Environment, 2022)

Runoff curve number-potential evapotranspiration-duration relationship for selected watersheds in Ethiopia - Henok Mekonnen Aragaw; Surendra Kumar Mishra (Modeling Earth Systems and Environment, 2022)

Investigation of jarosite-cement blends for hydration process and mechanical behavior in PQC mixes - Surendra Kumar Saini; G. D. Ransinchung; Praveen Kumar; Sonalisa Ray (Innovative Infrastructure Solutions, 2022)

GIS-based impact assessment and spatial distribution of air and water pollutants in mining area - Mukesh Ruhela; Kaberi Sharma; Rakesh Bhutiani; Surendra Kumar Chandniha; Vikas Kumar; Kaomud Tyagi; Faheem Ahamad; Inderjeet Tyagi (Environmental Science and Pollution Research, 2022)

Ice dynamics of Vestre Brøggerbreen glaciers, Ny-Ålesund, Svalbard, Arctic - Mohammad Sadiq; Sharat Dutta; Pradeep Kumar; Surendra Jat; Deepak Y Gajbhiye; Amit Dharwadkar (Journal of Earth System Science, 2022)

Clarification of issues and long-duration hydrologic simulation SCS-CN-based proxy modelling - Henok Mekonnen Aragaw; Surendra Kumar Mishra (Acta Geophysica, 2022)

Multi-site multi-objective calibration of SWAT model using a large dataset for improved performance in Ethiopia - Henok Mekonnen Aragaw; Surendra Kumar Mishra (Arabian Journal of Geosciences, 2022)

Spatiotemporal assessment of precipitation variability, seasonality, and extreme characteristics over a Himalayan catchment - Sabyasachi Swain; Surendra Kumar Mishra; Ashish Pandey; Deen Dayal (Theoretical and Applied Climatology, 2022)

Evaluation of Indian mustard (Brassica juncea L.) varieties for productivity, profitability, energetics and carbon dynamics under diverse irrigation regimes and sulphur application rates - Kiran Rana; Manoj Parihar; Jitendra Pratap Singh; Rajesh Kumar Singh; Surendra Singh Jatav; Utkarsh Kumar (Environmental Sustainability, 2021)

Actinomycetes isolates of arid zone of Indian Thar Desert and efficacy of their bioactive compounds against human pathogenic bacteria - Surendra Kumar; Dilip Singh Solanki; Khushbu Parihar; Alkesh Tak; Praveen Gehlot; Rakesh Pathak; Sunil Kumar Singh (Biologia Futura, 2021)

Geo-spatial analysis for horizontal and vertical variability of bulk density, particle-size distribution and soil moisture content in Tripura, Northeastern India - Sah Kausar Reza; Nirmal Kumar; Sundaram Ramachandran; Subrata Mukhopadhyay; Surendra Kumar Singh; Brahma S. Dwivedi; Sanjay Kumar Ray (Arabian Journal of Geosciences, 2021)

Assessing heavy metal accumulation in plants and soil with sewage sludge application under rice–wheat system in an Indo-Gangetic Inceptisol - Ashish Latare Marotrao; Satish Kumar Singh; Abhik Patra; Omkar Kumar; Surendra Singh Jatav; Shobh Nath Yadav (Arabian Journal of Geosciences, 2021)

Cross tolerance to phosphorus deficiency and drought stress in mungbean is regulated by improved antioxidant capacity, biological N2-fixation, and differential transcript accumulation - Surendra Kumar Meena; Renu Pandey; Sandeep Sharma; Gayacharan; Krishnapriya Vengavasi; Harsh Kumar Dikshit; Kadambot H. M. Siddique; Madan Pal Singh (Plant and Soil, 2021)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Geomorphic assessment of the factors contributing to the evolution of landforms in Ukhaldhunga area, Kosi River valley, Kumaun Himalaya, Uttarakhand - Khayingshing Luirei; Surendra S. Bhakuni; Limasanen Longkumer; Vipin Kumar; Imlirenla Jamir (Geosciences Journal, 2021)

A simple procedure for design flood estimation incorporating duration and return period of design rainfall - Ishan Sharma; Surendra Kumar Mishra; Ashish Pandey (Arabian Journal of Geosciences, 2021)

Cross-amplification of ungulate microsatellite markers in the endemic Indian antelope or blackbuck (Antilope cervicapra) for population monitoring and conservation genetics studies in south Asia - Rahul De; Vinay Kumar; Kumar Ankit; Khursid Alam Khan; Himanshu Kumar; Nirmal Kumar; Bilal Habib; Surendra Prakash Goyal (Molecular Biology Reports, 2021)

Induction of oxidative stress and apoptosis in the injured brain: potential relevance to brain regeneration in zebrafish - Surendra Kumar Anand; Manas Ranjan Sahu; Amal Chandra Mondal (Molecular Biology Reports, 2021)

SCS-CN-Based Improved Models for Direct Surface Runoff Estimation from Large Rainfall Events - Ravindra Kumar Verma; Sangeeta Verma; Surendra Kumar Mishra; Ashish Pandey (Water Resources Management, 2021)

Understanding the diversification pattern of three subspecies of swamp deer (Rucervus duvaucelii) during the Pleistocene–Holocene based on mitochondrial and Y chromosome markers - Ved Prakash Kumar; Bheem Dutt Joshi; Reeta Sharma; Ankita Rajpoot; Animesh Talukdar; Parag Nigam; Dhyanendra Kumar; Surendra Prakash Goyal (Mammalian Biology, 2021)

Hydrological responses to human-induced land use/land cover changes in the Gidabo River basin, Ethiopia - Henok Mekonnen Aragaw; Manmohan Kumar Goel; Surendra Kumar Mishra (Hydrological Sciences Journal, 2021)

UAV Remote Sensing for Campus Monitoring: A Comparative Evaluation of Nearest Neighbor and Rule-Based Classification - Anuj Tiwari; Surendra Kumar Sharma; Abhilasha Dixit; Vishal Mishra (Journal of the Indian Society of Remote Sensing, 2021)

Spatial–Spectral Image Classification with Edge Preserving Method - Suresh Merugu; Anuj Tiwari; Surendra Kumar Sharma (Journal of the Indian Society of Remote Sensing, 2021)

Infectious bovine abortions: observations from an organized dairy herd - Laxmi Narayan Sarangi; Nazia Tharani; Supriya Polapally; Samir Kumar Rana; Naveena Thodangala; Vijay Shriram Bahekar; Amitesh Prasad; Rachamreddy Venkata Chandrasekhar Reddy; Kota Sri Naga Leela Surendra; Hariprasad Naidu Gonuguntla; Nadikerianda Muthappa Ponnanna; Girish Kumar Sharma (Brazilian Journal of Microbiology, 2021)

Physiological Relevance of Angiotensin Converting Enzyme 2 As a Metabolic Linker and Therapeutic Implication of Mesenchymal Stem Cells in COVID-19 and Hypertension - Sarama Saha; Sasanka Chakrabarti; Praveen Kumar Singh; Jit Poddar; Soumitra Satapathi; Surendra Saini; Sham S. Kakar; Partha Roy (Stem Cell Reviews and Reports, 2021)

Delineating resource management domains of Yavatmal district using geospatial tools - Nitin Gorakh Patil; Vishnu Prakash Reddy; Surendra Kumar Singh (Arabian Journal of Geosciences, 2021)

RETRACTED ARTICLE: Modeling on Long term land use change detection Analysis of Kabul River Basin, Afghanistan by using geospatial techniques - Elyas Khairandish; Surendra Kumar Mishra; Anil Kumar Lohani (Modeling Earth Systems and Environment, 2020)

Assessment of frequency and severity of droughts in Maharashtra state of India - Kumar Amrit; Arti Roshan Soni; Sunayana; Surendra Kumar Mishra; Ritesh Vijay; Rakesh Kumar (Arabian Journal of Geosciences, 2020)

Image Stitching using AKAZE Features - Surendra Kumar Sharma; Kamal Jain (Journal of the Indian Society of Remote Sensing, 2020)

Synthesis and Characterization of Antimicrobial Silver Nanoparticles by an Endophytic Fungus Isolated from Nyctanthes arbor-tristis - Surendra Kumar Gond; Ashish Mishra; Satish Kumar Verma; Vijay Kumar Sharma; Ravindra Nath Kharwar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Culture selected somaclonal variants showing low-ODAP and high protein content in nineteen grass pea (Lathyrus sativus L.) genotypes - Surendra Barpete; Priyanka Gupta; Murari Singh; Shiv Kumar (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

The potential of arbuscular mycorrhizal fungi in C cycling: a review - Manoj Parihar; Amitava Rakshit; Vijay Singh Meena; Vijai Kumar Gupta; Kiran Rana; Mahipal Choudhary; Gopal Tiwari; Pankaj Kumar Mishra; Arunava Pattanayak; Jaideep Kumar Bisht; Surendra Singh Jatav; Priyanka Khati; et al. (Archives of Microbiology, 2020)

Assessment of spatio-temporal vegetation dynamics in tropical arid ecosystem of India using MODIS time-series vegetation indices - Gangalakunta P. Obi Reddy; Nirmal Kumar; Nisha Sahu; Rajeev Srivastava; Surendra Kumar Singh; Lekkala Gopala Krishnama Naidu; Gajjala Ravindra Chary; Chandrashekhar M. Biradar; Murali Krishna Gumma; Bodireddy Sahadeva Reddy; Javaji Narendra Kumar (Arabian Journal of Geosciences, 2020)

Study on the genetic variability and pathogenicity assessment among isolates of spot blotch causing fungi (Bipolaris sorokiniana) in wheat (Triticum aestivum L.) - Suneel Kumar Verma; Surendra Kumar Chaurasia; Yaswant Kumar Pankaj; Rajeev Kumar (Plant Physiology Reports, 2020)

G × E interactions in QTL introgression lines of Spanish-type groundnut (Arachis hypogaea L.) - A. L. Rathnakumar; Surendra S. Manohar; Hajisaheb L. Nadaf; Sudam C. Patil; Milind P. Deshmukh; P. P. Thirumalaisamy; Narendra Kumar; H. B. Lalwani; P. Nagaraju; Basavaraj Yenagi; S. S. Patil; J. Suryawanshi; et al. (Euphytica, 2020)

Trace elemental signatures and mineral chemistry of clays associated with the alteration halos of the Paleoproterozoic U mineralization in Bijawars of the Sonrai Basin, Central India - Surendra Kumar Jha; Rashmi Sharma; Jaya Prakash Shrivastava (Acta Geochimica, 2020)

A new record of gastroid fungus Broomeia congregata Berk. from Great Indian Thar Desert, India - Praveen Gehlot; Dilip Singh Solanki; Surendra Kumar; Khushbu Parihar; Alkesh Tak; Rakesh Pathak; Sunil Kumar Singh (Indian Phytopathology, 2020)

Retraction Note to: Inferring Phylogenetic Relationships of Indian Citron (Citrus medica L.) Based on rbcL and matK Sequences of Chloroplast DNA - Ajit Uchoi; Surendra Kumar Malik; Ravish Choudhary; Susheel Kumar; M. R. Rohini; Digvender Pal; Sezai Ercisli; Rekha Chaudhury (Biochemical Genetics, 2020)

A study of comorbidities in myasthenia gravis - Usha K. Misra; Jayantee Kalita; Varun K. Singh; Surendra Kumar (Acta Neurologica Belgica, 2020)

The Study of Morphological Characteristics for Best Management Practices Over the Rampur Watershed of Mahanadi River Basin Using Prioritization - Priyanka Gunjan; S. K. Mishra; Anil Kumar Lohani; Surendra Kumar Chandniha (Journal of the Indian Society of Remote Sensing, 2020)

Characterization of Pseudofusicoccum adansoniae, an Endophytic Fungus Residing in Photosynthetic Root of Tinospora cordifolia, a Medicinal Plant - Ashish Mishra; Surendra K. Gond; Vijay K. Sharma; Satish K. Verma; Jitendra Kumar; Dheeraj K. Singh; Anuj Kumar; Pooja Pandey; R. N. Kharwar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Investigating the genetic diversity and presence of forensically informative nucleotide sequences in Indian antelope (Antilope cervicapra) using multiple genes of the mitochondrial genome - Malay Ashvinkumar Shukla; Bheem Dutt Joshi; Ved Prakash Kumar; Anil Kumar Mehta; Surendra Prakash Goyal (Molecular Biology Reports, 2019)

Hemin attenuated oxidative stress and inflammation to improve wound healing in diabetic rats - Dhirendra Kumar; Geeta Rani Jena; Mahendra Ram; Madhu Cholenahalli Lingaraju; Vishakha Singh; Raju Prasad; Sanjay Kumawat; Vinay Kant; Priyanka Gupta; Surendra Kumar Tandan; Dinesh Kumar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Delineation of spring recharge zones using environmental isotopes to support climate-resilient interventions in two mountainous catchments in Far-Western Nepal - Karthikeyan Matheswaran; Ambika Khadka; Sanita Dhaubanjar; Luna Bharati; Sudhir Kumar; Surendra Shrestha (Hydrogeology Journal, 2019)

Perturbations in Earth’s Atmosphere over An Indian Region during the Total Solar Eclipse on 22 July 2009 - S. B. Surendra Prasad; Vinay Kumar; K. Krishna Reddy; S. K. Dhaka; Shristy Malik; M. Venkatarami Reddy; U. Murali Krishna (Journal of Meteorological Research, 2019)

Antioxidant Potentiality and Mineral Content of Summer Season Leafy Greens: Comparison at Mature and Microgreen Stages Using Chemometric - Lalu Prasad Yadav; Tanmay Kumar Koley; Ajay Tripathi; Surendra Singh (Agricultural Research, 2019)

Comparative analysis for understanding salinity tolerance mechanism in Indian Mustard (Brassica juncea L.) - Binay K. Singh; Surendra P. Singh; Kapila Shekhawat; Sanjay S. Rathore; Avinash Pandey; Sudhir Kumar; Devendra K. Singh; Shashi Bhushan Choudhry; Saurav Kumar; Dhiraj Singh (Acta Physiologiae Plantarum, 2019)

Regional scale analysis of trends in rainfall using nonparametric methods and wavelet transforms over a semi‐arid region in India - Lalit Pal; Chandra Shekhar P. Ojha; Surendra K. Chandniha; Amit Kumar (International Journal of Climatology, 2019)
Space‐time variability of rainfall at local scale is affected by several regional factors such as aerosol concentration, greenhouse gases, land cover changes, etc., along with large scale atmospheric circulations. Predictive ability of regional circulation models can be significantly improved and efficient management of water resources can be assured by identifying dominant variables controlling spatiotemporal variations in rainfall among aforementioned factors. The present study aims to investigate dominant climate system(s) controlling trends in rainfall over Chhattisgarh state (a semi‐arid region) in India over the period of 115 years (1901–2015). Discrete wavelet transform in conjunction with Mann–Kendall test is applied to the rainfall data series at different time scales (monthly, seasonal, annual, pre‐monsoon, monsoon, post‐monsoon and winter) in order to identify the long term trends and dominant periodic components influencing the trend. In the results, negative trends are found to exist in all rainfall time series at majority of districts (except for annual and monsoon rainfall at Bijapur and Sukma district). In addition, analysis of trend in actual evapotranspiration and soil moisture in the region does not exhibits the effect of anthropogenic variables (such as land cover change, irrigation projects, etc.) on the rainfall as significant negative trend are also observed in soil moisture for majority of districts. Overall, 2‐year and 4‐year periodic components have been detected to be dominating the trends in most of the rainfall time series (annual, monsoon, post‐monsoon and winter). On comparing the identified dominating components with the existing climate systems (Atlantic multidecadal oscillations, Indian ocean dipole, Madden‐Julian oscillations, Inter‐Tropical Convergence Zone, etc.), El Niño‐Southern Oscillations has been recognized as predominant climate circulation influencing the rainfall trends over the study region. The study outcomes are expected to improve the regional precipitation forecasts and should be useful in various hydro‐meteorological analyses and decision making at regional scale.

Effective synthesis of some novel pyrazolidine-3,5-dione derivatives via Mg(II) catalyzed in water medium and their anticancer and antimicrobial activities - Meera Moydeen; Radhakrishnan Surendra Kumar; Akbar Idhayadhulla; Aseer Manilal (Molecular Diversity, 2019)

Assessment of meteorological drought characteristics over Central India - Kumar Amrit; Rajendra P. Pandey; Surendra K. Mishra (Sustainable Water Resources Management, 2018)

Characterization of MAR and heavy metal-tolerant E. coli O157:H7 in water sources: a suggestion for behavioral intervention - Shailendra Kumar; Vinayak Ram Tripathi; Surendra Vikram; Bipul Kumar; Satyendra Kumar Garg (Environment, Development and Sustainability, 2018)

Characteristics of meteorological droughts in northwestern India - Kumar Amrit; Rajendra P. Pandey; Surendra K. Mishra (Natural Hazards, 2018)

Simplified SMA-inspired 1-parameter SCS-CN model for runoff estimation - Sangeeta Verma; Pushpendra Kumar Singh; Surendra Kumar Mishra; Sanjay Kumar Jain; Ronny Berndtsson; Anju Singh; Ravindra Kumar Verma (Arabian Journal of Geosciences, 2018)

Relationship of drought frequency and severity with range of annual temperature variation - Kumar Amrit; Rajendra P. Pandey; Surendra K. Mishra; Mihail Daradur (Natural Hazards, 2018)

Priority Zoning of Available Micronutrients in the Soils of Agro-ecological Sub-regions of North-East India Using Geo-spatial Techniques - Siladitya Bandyopadhyay; Prasenjit Ray; Shelton Padua; S. Ramachandran; Roomesh Kumar Jena; Partha Deb Roy; D. P. Dutta; Surendra Kumar Singh; Sanjay Kumar Ray (Agricultural Research, 2018)

Impact Assessment of GIS Based Land Resource Inventory Towards Optimizing Agricultural Land Use Plan in Dandakaranya and Easternghats Physiographic Confluence of India - Birendra Nath Ghosh; Krishnendu Das; Siladitya Bandyopadhyay; Subrata Mukhopadhyay; Dulal Chandra Nayak; Surendra Kumar Singh (Journal of the Indian Society of Remote Sensing, 2018)

Betulinic acid alleviates dextran sulfate sodium-induced colitis and visceral pain in mice - Jaspreet Kalra; Madhu Cholenahalli Lingaraju; Karikalan Mathesh; Dhirendra Kumar; Subhashree Parida; Thakur Uttam Singh; Anil Kumar Sharma; Dinesh Kumar; Surendra Kumar Tandan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Defective Wnt3 expression by testicular Sertoli cells compromise male fertility - Sayon Basu; Satya Pal Arya; Abul Usmani; Bhola Shankar Pradhan; Rajesh Kumar Sarkar; Nirmalya Ganguli; Mansi Shukla; Kamal Mandal; Surendra Singh; Kanchan Sarda; Subeer S. Majumdar (Cell and Tissue Research, 2018)

Human Saliva for Oral Precancer Detection: a Comparison of Fluorescence & Stokes Shift Spectroscopy - Pavan Kumar; Ashutosh Singh; Surendra Kumar Kanaujia; Asima Pradhan (Journal of Fluorescence, 2018)

Mapping groundwater recharge potential using GIS approach in Darwha block - Nitin Patil; Vishnu Prakash Reddy; Anurag Patangray; Surendra Kumar Singh (Arabian Journal of Geosciences, 2018)

Urban water service quality assessment in Tanzanian towns of Songea and Mbeya - Mitthan Lal Kansal; Ivor Joseph Ndimbo; Surendra Kumar Chandaniha (Sustainable Water Resources Management, 2017)

Trend analysis of precipitation in Jharkhand State, India - Surendra Kumar Chandniha; Sarita Gajbhiye Meshram; Jan Franklin Adamowski; Chandrashekhar Meshram (Theoretical and Applied Climatology, 2017)

Phenetic and genetic diversity in Indian Luffa (Cucurbitaceae) inferred from morphometric, ISSR and DAMD markers - Sujata Misra; Awadhesh Kumar Srivastava; Sushma Verma; Sudhakar Pandey; Surendra Singh Bargali; Tikam Singh Rana; K. Narayanan Nair (Genetic Resources and Crop Evolution, 2017)

2,4-Disubstituted thiazoles as multitargated bioactive molecules - Preeti Arora; Rakesh Narang; Surendra Kumar Nayak; Sachin Kumar Singh; Vikramjeet Judge (Medicinal Chemistry Research, 2016)

Integrated Geophysical and Geochemical Assessment for the Comprehensive Study of the Groundwater - Krishna Kumar Kotra; Israel Yedluri; Surendra Prasad; Sowjanya Pasupureddi (Water, Air, & Soil Pollution, 2016)

Role of common sarcomeric gene polymorphisms in genetic susceptibility to left ventricular dysfunction - SURENDRA KUMAR; AVSHESH MISHRA; ANSHIKA SRIVASTAVA; MANSI BHATT; N. GARG; S. K. AGARWAL; SHANTANU PANDE; BALRAJ MITTAL (Journal of Genetics, 2016)

RETRACTED ARTICLE: Inferring Phylogenetic Relationships of Indian Citron (Citrus medica L.) based on rbcL and matK Sequences of Chloroplast DNA - Ajit Uchoi; Surendra Kumar Malik; Ravish Choudhary; Susheel Kumar; M. R. Rohini; Digvender Pal; Sezai Ercisli; Rekha Chaudhury (Biochemical Genetics, 2016)

Support vector machine and fuzzy C-mean clustering-based comparative evaluation of changes in motor cortex electroencephalogram under chronic alcoholism - Surendra Kumar; Subhojit Ghosh; Suhash Tetarway; Rakesh Kumar Sinha (Medical & Biological Engineering & Computing, 2015)

Anti-inflammatory and chondroprotective effects of atorvastatin in a cartilage explant model of osteoarthritis - Nitya N. Pathak; Madhu C. Lingaraju; Venkanna Balaganur; Vinay Kant; Amar S. More; Dhirendra Kumar; Dinesh Kumar; Surendra K. Tandan (Inflammation Research, 2015)

Activation of oxidative stress and inflammatory factors could account for histopathological progression of aflatoxin-B1 induced hepatocarcinogenesis in rat - Krishna Beer Singh; Brajesh Kumar Maurya; Surendra Kumar Trigun (Molecular and Cellular Biochemistry, 2015)

Topomer-CoMFA-based predictive modelling on 2,3-diaryl-substituted-1,3-thiazolidin-4-ones as non-nucleoside reverse transcriptase inhibitors - Surendra Kumar; Meena Tiwari (Medicinal Chemistry Research, 2015)

Pannexin1 as a novel cerebral target in pathogenesis of hepatic encephalopathy - Papia Mondal; Surendra Kumar Trigun (Metabolic Brain Disease, 2014)

Uptake and Distribution of Iron from Different Iron Sources Applied as Foliar Sprays to Chlorotic Leaves of Low-Chill Peach Cultivars - Binayak Chakraborty; Pramod Narayan Singh; Surendra Kumar; Prakash Chandra Srivastava (Agricultural Research, 2014)

Antioxidant potential of bilirubin-accelerated wound healing in streptozotocin-induced diabetic rats - Mahendra Ram; Vishakha Singh; Dhirendra Kumar; Sanjay Kumawat; Anu Gopalakrishnan; Madhu C. Lingaraju; Priyanka Gupta; Surendra Kumar Tandan; Dinesh Kumar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Comparative transcriptome analysis of ovules reveals stress related genes associated with nucellar polyembryony in citrus - Vajinder Kumar; Surendra Kumar Malik; Digvender Pal; Ramamurthy Srinivasan; Shripad Ramachandra Bhat (Tree Genetics & Genomes, 2014)

Root carboxylate exudation capacity under phosphorus stress does not improve grain yield in green gram - Renu Pandey; Surendra Kumar Meena; Vengavasi Krishnapriya; Altaf Ahmad; Naval Kishora (Plant Cell Reports, 2014)

Apoptosis of Dalton’s lymphoma due to in vivo treatment with emodin is associated with modulations of hydrogen peroxide metabolizing antioxidant enzymes - Krishna Beer Singh; Surendra Kumar Trigun (Cell Biochemistry and Biophysics, 2013)

Moderate grade hyperammonemia activates lactate dehydrogenase-4 and 6-phosphofructo-2-kinase to support increased lactate turnover in the brain slices - Aditi Mehrotra; Surendra Kumar Trigun (Molecular and Cellular Biochemistry, 2013)

Influence of salicylic acid and methyl jasmonate elicitation on anthocyanin production in callus cultures of Rosa hybrida L. - Mohan Ram; K. V. Prasad; S. K. Singh; B. S. Hada; Surendra Kumar (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Genetic mapping and QTL analysis for sugar yield-related traits in sugarcane - Ram Kushal Singh; Sujeet Pratap Singh; Dinesh Kumar Tiwari; Shraddha Srivastava; Surendra Bahadur Singh; Mukut Lal Sharma; Rakesh Singh; Trilochan Mohapatra; Nagendra Kumar Singh (Euphytica, 2013)

Plasma hormones, metabolites, milk production, and cholesterol levels in Murrah buffaloes fed with Asparagus racemosus in transition and postpartum period - Surendra Pratap Singh; Ram Kumar Mehla; Mahendra Singh (Tropical Animal Health and Production, 2012)

Effect of S-methylisothiourea in acetaminophen-induced hepatotoxicity in rat - Amar S. More; Rashmi R. Kumari; Gaurav Gupta; Kandasamy Kathirvel; Milindmitra K. Lonare; Rohini S. Dhayagude; Dhirendra Kumar; Dinesh Kumar; Anil K. Sharma; Surendra K. Tandan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Synthesis and anticonvulsant activity of some new series of pyrrole derivatives - A. Idhayadhulla; R. Surendra Kumar; A. Jamal Abdul Nasser; S. Kavimani; S. Indumathy (Medicinal Chemistry Research, 2012)

Design, synthesis, and anticonvulsant evaluation of some novel 1, 3 benzothiazol-2-yl hydrazones/acetohydrazones - Praveen Kumar; Birendra Shrivastava; Surendra N. Pandeya; Laxmi Tripathi; James P. Stables (Medicinal Chemistry Research, 2012)

Structural studies on ligand–DNA systems: A robust approach in drug design - Surat Kumar; Prateek Pandya; Kumud Pandav; Surendra P Gupta; Arun Chopra (Journal of Biosciences, 2012)

Homologous Recombination is Activated at Early Time Points Following Exposure to Cobalt Chloride Induced Hypoxic Conditions in Saccharomyces cerevisiae - Ramesh Chand Meena; Navin Kumar; Surendra Nath; Amitabha Chakrabarti (Indian Journal of Microbiology, 2012)

High consistency between replicate 454 pyrosequencing analyses of ectomycorrhizal plant root samples - Håvard Kauserud; Surendra Kumar; Anne K. Brysting; Jenni Nordén; Tor Carlsen (Mycorrhiza, 2012)

Changes in the root‐associated fungal communities along a primary succession gradient analysed by 454 pyrosequencing - RAKEL BLAALID; TOR CARLSEN; SURENDRA KUMAR; RUNE HALVORSEN; KARL INNE UGLAND; GIOVANNI FONTANA; HÅVARD KAUSERUD (Molecular Ecology, 2012)
We investigated changes in the root‐associated fungal communities associated with the ectomycorrhizal herb Bistorta vivipara along a primary succession gradient using 454 amplicon sequencing. Our main objective was to assess the degree of variation in fungal richness and community composition as vegetation cover increases along the chronosequence. Sixty root systems of B. vivipara were sampled in vegetation zones delimited by dated moraines in front of a retreating glacier in Norway. We extracted DNA from rinsed root systems, amplified the ITS1 region using fungal‐specific primers and analysed the amplicons using 454 sequencing. Between 437 and 5063 sequences were obtained from each root system. Clustering analyses using a 98.5% sequence similarity cut‐off yielded a total of 470 operational taxonomic units (OTUs), excluding singletons. Between eight and 41 fungal OTUs were detected within each root system. Already in the first stage of succession, a high fungal diversity was present in the B. vivipara root systems. Total number of OTUs increased significantly along the gradient towards climax vegetation, but the average number of OTUs per root system stayed unchanged. There was a high patchiness in distribution of fungal OTUs across root systems, indicating that stochastic processes to a large extent structure the fungal communities. However, time since deglaciation had impact on the fungal community structure, as a systematic shift in the community composition was observed along the chronosequence. Ectomycorrhizal basidiomycetes were the dominant fungi in the roots of B. vivipara, when it comes to both number of OTUs and number of sequences.

QSAR modeling of the inhibition of reverse transcriptase enzyme with benzimidazolone analogs - Surendra Kumar; Vineet Singh; Meena Tiwari (Medicinal Chemistry Research, 2011)

Search of antimycobacterial activities in hybrid molecules with benzopyran skeleton - Rama P. Tripathi; Surendra Singh Bisht; Vivek Parashar Pandey; Sarvesh K. Pandey; Shubhra Singh; Sudhir Kumar Sinha; Vinita Chaturvedi (Medicinal Chemistry Research, 2011)

Salutary Effect of Cassia auriculata L. Leaves on Hyperglycemia-Induced Atherosclerotic Environment in Streptozotocin Rats - Shipra Gupta; Suman Bala Sharma; Usha Rani Singh; Surendra Kumar Bansal (Cardiovascular Toxicology, 2011)

Endophytic Fungal Flora from Roots and Fruits of an Indian Neem Plant Azadirachta indica A. Juss., and Impact of Culture Media on their Isolation - Vijay C. Verma; Surendra K. Gond; Anuj Kumar; Ravindra N. Kharwar; Lori-Ann Boulanger; Gary A. Strobel (Indian Journal of Microbiology, 2011)

Assessment of diversity, distribution and antibacterial activity of endophytic fungi isolated from a medicinal plant Adenocalymma alliaceum Miers - Ravindra N. Kharwar; Satish K. Verma; Ashish Mishra; Surendra K. Gond; Vijay K. Sharma; Talat Afreen; Anuj Kumar (Symbiosis, 2011)

Wound healing activity of carbon monoxide liberated from CO-releasing molecule (CO-RM) - Azad Ahmad Ahanger; Shahid Prawez; Dhirendra Kumar; Raju Prasad; Amarpal; Surendra Kumar Tandan; Dinesh Kumar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Pharmacogenetic Aspects of Coumarinic Oral Anticoagulant Therapies - Saurabh Singh Rathore; Surendra Kumar Agarwal; Shantanu Pande; Sushil Kumar Singh; Tulika Mittal; Balraj Mittal (Indian Journal of Clinical Biochemistry, 2011)

Induction of anthocyanin pigments in callus cultures of Rosa hybrida L. in response to sucrose and ammonical nitrogen levels - Mohan Ram; K. V. Prasad; Charanjit Kaur; S. K. Singh; Ajay Arora; Surendra Kumar (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

A validated HPTLC method for determination of trans -caryophyllene from polyherbal formulations - Kartik Chandra Patra; Brijesh Singh; Surendra Pareta; K. Jayaram Kumar (Natural Product Research, 2010)

Pre-bleaching of mixed hardwood pulp with sulphuric acid - D. Weley Siddhartha; Pradeep Kumar; Surendra P. Singh (Journal of the Indian Academy of Wood Science, 2010)

Novel mutation in ATP-binding domain of ABCD1 gene in adrenoleucodystrophy - Neeraj Kumar; Krishna K. Taneja; Atul Kumar; Deepti Nayar; Bhupesh Taneja; Satindra Aneja; Madhuri Behari; Veena Kalra; Surendra K. Bansal (Journal of Genetics, 2010)

A comparative study of endophytic and epiphytic fungal association with leaf of Eucalyptus citriodora Hook., and their antimicrobial activity - Ravindra N. Kharwar; Surendra K. Gond; Anuj Kumar; Ashish Mishra (World Journal of Microbiology and Biotechnology, 2010)

Comparative study of a Zn-enriched post-methanation bio-sludge and Zn sulfate as Zn sources for a rice–wheat crop rotation - Prakash C. Srivastava; Ajay P. Singh; Surendra Kumar; V. Ramachandran; Manoj Shrivastava; S. F. D’souza (Nutrient Cycling in Agroecosystems, 2009)

Evaluation of protective efficacy of Spirulina platensis against collagen-induced arthritis in rats - Narendra Kumar; Surendra Singh; Nisha Patro; Ishan Patro (Inflammopharmacology, 2009)

Javanicin, an Antibacterial Naphthaquinone from an Endophytic Fungus of Neem, Chloridium sp. - Ravindra N. Kharwar; Vijay C. Verma; Anuj Kumar; Surendra K. Gond; James K. Harper; Wilford M. Hess; Emil Lobkovosky; Cong Ma; Yuhao Ren; Gary A. Strobel (Current Microbiology, 2009)

Desorption and transformation of zinc in a mollisol and its uptake by plants in a rice–wheat rotation fertilized with either zinc-enriched biosludge from molasses or with inorganic zinc - Prakash C. Srivastava; Ajay P. Singh; Surendra Kumar; V. Ramachandran; Manoj Shrivastava; S. F. D’souza (Biology and Fertility of Soils, 2008)

Metal Cu(II) and Zn(II) bipyridyls as inhibitors of lactate dehydrogenase - Raj Kumar Koiri; Surendra Kumar Trigun; Santosh Kumar Dubey; Santosh Singh; Lallan Mishra (BioMetals, 2008)

Analysis of square and rectangular footings subjected to eccentric-inclined load resting on reinforced sand - Swami Saran; Surendra Kumar; K.G. Garg; Arvind Kumar (Geotechnical and Geological Engineering, 2007)

Influence of L-lysine and zinc administration during exposure to lead or lead and ethanol in rats - Sushil Kumar Tandon; Surendra Singh; Satgur Prasad; Neeraj Mathur (Biological Trace Element Research, 1997)